The impact of clinical and social factors on the physical health of people with severe mental illness: Results from an Italian multicentre study. (September 2021) - Luciano, Mario; Sampogna, Gaia; Del Vecchio, Valeria; Giallonardo, Vincenzo; Palummo, Carmela; Andriola, Ileana; Amore, Mario; Rossi, Rodolfo; Carmassi, Claudia; Siracusano, Alberto; Fiorillo, Andrea; ,
Highlights: Internalized stigma correlates with all the analysed physical health parameters. The other most important factor significantly associated with a poor physical health is a poor quality of life, which is associated with BMI, waist circumference, CIRS comorbidity and severity indexes and cardiovascular risk score. Psychiatric symptoms more strongly associated with poor physical health are depressive/anxiety and manic symptoms at BPRS. No differences in the cardiometabolic parameters have been found among patients with schizophrenia, bipolar disorder and major depression. Abstract: Our manuscript aims to: 1) assess physical health in a sample of patients with severe mental disorders; and 2) identify the psychopathological and psychosocial characteristics associated with an increased likelihood of having a poor physical health. The study, funded by the Italian Ministry of Education, has been carried out in psychiatric outpatient units of six Italian University sites. All recruited patients have been assessed through standardized assessment instruments. Moreover, anthropometric parameters have been obtained at recruitment and a blood samples have been collected to assess cardiometabolic parameters. Four-hundred and two patients with a primary diagnosis of bipolar disorder (43.3%), schizophrenia or other psychotic disorder (29.9%), or major depression (26.9%) were recruited. Internalized stigma, psychosocial functioning, quality of life, psychiatric hospitalizations, depressive/anxiety and manic symptoms and cognition were those domains more strongly associated with poor metabolic parameters, including high body mass index, HOMA and Framingham indexes and waist circumference. There were no statistically significant differences among the three diagnostic groups. Our findings highlight the importance of perceived stigma and quality of life on patients' physical health. This should be taken into account when developing plans for reducing the mortality rate in patients with severe mental disorders.